Out-of-pocket payments in the Austrian healthcare system: A distributional analysis - Alice Sanwald; Engelbert Theurl (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2015)
Introduction: Out-of-pocket spending is an important source of healthcare financing even in countries with established prepaid financing of healthcare. However, out-of-pocket payments (OOPP) may have undesirable effects from an equity perspective. In this study, we analyse the distributive effects of OOPP in Austria based on cross-sectional information from the Austrian Household Budget Survey 2009/10. Methods: We combine evidence from disaggregated measures (concentration curve and Lorenz curve) and summary indices (Gini coefficient, Kakwani index, and Reynolds-Smolensky index) to demonstrate the distributive effects of total OOPP and their subcomponents. Thereby, we use different specifications of household ability to pay. We follow the Aronson-Johnson-Lampert approach and split the distributive effect into its three components: progressivity, horizontal equity, and reranking. Results: OOPP in Austria have regressive effects on income distribution. These regressive effects are especially pronounced for the OOPP category prescription fees and over-the-counter pharmaceuticals. Disaggregated evidence shows that the effects differ between income groups. The decomposition analysis reveals a high degree of reranking and horizontal inequity for total OOPP, and particularly, for therapeutic aids and physician services. Conclusions: The results - especially those for prescription fees and therapeutic aids - are of high relevance for the recent and on-going discussion on the reform of benefit catalogues and cost-sharing schemes in the public health insurance system in Austria.
Keywords: H22; H23; H51; I14; 330; out-of-pocket health expenditure; healthcare financing inequalities; Kakwani index; vertical equity; horizontal equity; reranking